The plasma environment of comet 67P/Churyumov-Gerasimenko - Goetz,C; Behar,E; Beth,A; Bodewits,D; Bromley,S; Burch,J; Deca,J; Divin,A; Eriksson,AI; Feldman,PD; Galand,M; Gunell,H; et al. (Space Science Reviews, 2022)
The environment of a comet is a fascinating and unique laboratory to study plasma processes and the formation of structures such as shocks and discontinuities from electron scales to ion scales and above. The European Space Agency’s Rosetta mission collected data for more than two years, from the rendezvous with comet 67P/Churyumov-Gerasimenko in August 2014 until the final touch-down of the spacecraft end of September 2016. This escort phase spanned a large arc of the comet’s orbit around the Sun, including its perihelion and corresponding to heliocentric distances between 3.8 AU and 1.24 AU. The length of the active mission together with this span in heliocentric and cometocentric distances make the Rosetta data set unique and much richer than sets obtained with previous cometary probes. Here, we review the results from the Rosetta mission that pertain to the plasma environment. We detail all known sources and losses of the plasma and typical processes within it. The findings from in-situ plasma measurements are complemented by remote observations of emissions from the plasma. Overviews of the methods and instruments used in the study are given as well as a short review of the Rosetta mission. The long duration of the Rosetta mission provides the opportunity to better understand how the importance of these processes changes depending on parameters like the outgassing rate and the solar wind conditions. We discuss how the shape and existence of large scale structures depend on these parameters and how the plasma within different regions of the plasma environment can be characterised. We end with a non-exhaustive list of still open questions, as well as suggestions on how to answer them in the future.